2020
DOI: 10.1007/s11661-020-05931-w
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution and Recrystallization Resistance of a 7055 Alloy Fabricated by Spray Forming Technology and by Conventional Ingot Metallurgy

Abstract: The effect of different fabricating processes (spray forming and conventional casting) and homogenization treatment on the microstructure of an 7055 alloy was investigated by optical microscopy (OM), scanning electron microscopy (SEM), electron probe X-ray micro-analyzer (EPMA), and transmission electron microscopy (TEM). It was found that the grain size of the as-deposited (spray formed) 7055 alloy had half the size as that of the as-cast 7055 alloy and there was no Al 2 CuMg phase that embedded in the coarse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 28 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…When the alloy is deformed at low temperature, a large storage distortion energy is formed, which drives more vigorous dynamic recrystallization or static recrystallization. It can be seen from the literature that dynamic recrystallization of aluminum alloy is not easy to occur, so these recrystallized grains are likely to be formed by static recrystallization during solid solution heat treatment [7][8][9]. When the alloy is deformed at high temperature, the storage deformation energy is too low to drive static recrystallization, instead of dynamic recovery and static recovery.…”
Section: Resultsmentioning
confidence: 99%
“…When the alloy is deformed at low temperature, a large storage distortion energy is formed, which drives more vigorous dynamic recrystallization or static recrystallization. It can be seen from the literature that dynamic recrystallization of aluminum alloy is not easy to occur, so these recrystallized grains are likely to be formed by static recrystallization during solid solution heat treatment [7][8][9]. When the alloy is deformed at high temperature, the storage deformation energy is too low to drive static recrystallization, instead of dynamic recovery and static recovery.…”
Section: Resultsmentioning
confidence: 99%
“…This approach resulted in superior mechanical properties, specifically, a yield strength of 608 MPa, a tensile strength of 667 MPa, and an elongation of 10%, respectively. Furthermore, Xie et al [9] found that due to the characteristics of the spray-forming process, compared with traditional cast Al-Zn-Mg-Cu alloys, the homogenization of spray-formed alloys will result in a more uniform distribution and smaller size of the Al 3 Zr dispersed phases, which better inhibits the occurrence of recrystallization. Figure 8 shows the grain structure after the hot extrusion of spray-formed and traditional cast 7055 aluminum alloys after homogenization.…”
Section: Homogenizationmentioning
confidence: 99%
“…It is generally accepted that the addition of 0.05-0.15 wt.% Zr can result in the formation of the fine intermetallic compound Al 3 Zr [134]. It was noted by Xie et al [9] that the distribution of Zr within the grain is uneven in the as-cast 7055 alloy, while it is uniformly distributed in the spray-formed 7055 alloy billet. This disparity results in differences in the precipitation behavior of Al 3 Zr after two-stage homogenization at 350 • C/5 h + 470 • C/24 h (at a heating rate of 30 • C/h).…”
Section: Dispersoidsmentioning
confidence: 99%
See 1 more Smart Citation